Prevalence of Gingivitis in Second Trimester of Pregnancy - Shrestha, R.; Pradhan, S.; Baral, G. (Kathmandu University Medical Journal, 2022)
Background Gingivitis simply means the inflammation of gingiva. It is a reversible state but can lead to periodontitis. The final result could be the exfoliation of the tooth causing decreased masticatory function leading to a compromised quality of life. Gingivitis in the pregnant woman should be carefully assessed and treated and given special attention. There is rare documentation on the prevalence of gingivitis in pregnancy in the least developed countries. Objective To evaluate the prevalence of gingivitis in the second trimester of pregnancy and assess its relationship with age, parity, education, occupation, gravidity, oral hygiene habit and frequency of brushing. Method An observational descriptive study was conducted among 384 pregnant females in their second trimester in Kathmandu, Nepal. Demographic variables and general information including those related to oral hygiene practices and habits were collected during an interview. Plaque index and Gingival Index was recorded among the patients through full mouth examination at four sites. Result The prevalence of gingivitis in the second trimester of pregnancy was 76.3%. Statistically significant relationship was found between gingivitis and gravida and parity. A relation could not be established between gingivitis with age, education, occupation, oral hygiene habit and frequency of brushing. Conclusion The prevalence of gingivitis is found to be high in Nepalese pregnant women. Special strategies should be introduced targeting the pregnant women of least developed countries to uplift their periodontal health.